Charge Transfer Interaction Between Styrene Maleic Anhydride With Dimethyl Sulphoxide: Characterization and Histopathology of The Product - Singh, Amarika; Singh Rajput, Ravish (Asian Journal of Chemistry, 2010)
Styrene maleic anhydride co-polymer (SMA) belongs to a group of vinylic polymers. It follows the complex radical polymerization of vinyl aromatic styrene (donor) and maleic anhydride (acceptor). This co-polymer mixed with dimethyl sulphoxide in (1:2) ratio leads to its transformation, charge transfer interaction with dimethyl sulphoxide and form a polymer complex gel. It was found that the dissolution of co-polymer in dimethyl sulphoxide leads to its transformation on charge transfer interaction with dimethyl sulphoxide and subsequent Pummerer rearrangement. The detailed structural study of the polymer complex was done by using molecular spectroscopy. The co-polymer complex shows bio-medical property as it effects on the erythrocyte, Hb, TLC, DLC, platelets, etc.